Fabrication of a hybrid ultrafiltration membrane based on MoS2 modified with dopamine and polyethyleneimine. Issue 42 (2nd August 2021) - Wen, Xin; He, Can; Hai, Yuyan; Liu, Xiaofan; Ma, Rui; Sun, Jianyu; Yang, Xue; Qi, Yunlong; Chen, Jingyun; Wei, Hui
Abstract : The hydrophobicity of ultrafiltration membranes is the main cause of membrane fouling and reduced permeability, so it is necessary to improve the hydrophilicity and anti-fouling performance of ultrafiltration membrane materials. Abstract : The hydrophobicity of ultrafiltration membranes is the main cause of membrane fouling and reduced permeability, so it is necessary to improve the hydrophilicity and anti-fouling performance of ultrafiltration membrane materials. MoS2 nanoparticles that were modified with polydopamine (PDA) and polyethyleneimine (PEI), named MoS2 -PDA-PEI, were added to fabricate a polyethersulfone ultrafiltration membrane (PES/MoS2 -PDA-PEI) for the first time. The effects of modified MoS2 nanoparticles on membrane performance were clarified. The results indicated that the permeability, rejection, and anti-fouling capability of the hybrid PES/MoS2 -PDA-PEI membrane have been improved compared with the pristine PES membrane. When the content of MoS2 -PDA-PEI nanoparticles in the membrane is 0.5%, the pure water flux of the hybrid membrane reaches 364.03 L m −2 h −1, and the rejection rate of bovine serum albumin (BSA) and humic acid (HA) is 96.5% and 93.2% respectively. The flux recovery rate of HA reached 97.06%. As expected, the addition of MoS2 -PDA-PEI nanoparticles promotes the formation of the porous structure and improves the hydrophilicity of the membrane, thereby improving its antifouling performance.